Employee drug testing: are cities complying with the courts? - Fine, Cory R.; Reeves, T. Zane; Harney, George P. (Public Administration Review)
A national survey of cities was conducted in order to determine the degree to which all drug-testing policies and programs comply with privacy protections ordered by the Supreme Court and the ramification of noncompliance with court guidelines to legally agreed-upon employment rights in those same municipalities. The results indicate that constitutional concerns regarding the protection of employees from unnecessary invasions of privacy, unlawful searches and seizures, self-incrimination, and loss of employment were frequently secondary to the public's perceived need for an efficiently run and safe bureaucracy. A summary of the history of drug testing in the workplace is presented; the current status of precedent-setting case law is analyzed; and an agenda for further research is outlined.